The Role Of Local Culinary Innovation In Supporting Regional Branding In Gresik Regency - Bawa Mulyono Hadi; Ivy Dian P. Prabowo; Achmad Taufiq (Jurnal Ilmu Sosial dan Humaniora, 2026)
The development of experience-based tourism has driven local culinary offerings to become one of the strategic elements in shaping destination identity and image. Gresik Regency has a variety of distinctive culinary products with the potential to be developed as part of a regional branding strategy, but their utilization has not yet been optimally integrated with regional tourism and creative economy development. This study aims to analyze the forms of local culinary innovation in Gresik Regency, examine its role in supporting regional branding, and formulate a regional branding development model based on local culinary innovation. The study uses a descriptive qualitative approach with a case study strategy. Data were obtained through in-depth interviews, field observation, and documentation studies involving culinary MSME actors, local government, tourism destination managers, academics, and tourists. Data analysis was conducted using thematic analysis with the stages of coding, theme grouping, interpretation, and data triangulation. The results show that local culinary innovation develops across four main dimensions, namely product innovation, process innovation, packaging innovation, and digital marketing innovation. Field findings reveal that this innovation is manifested through product development, the use of packaging that highlights local cultural elements, the application of process standardization, and the utilization of social media in culinary promotion, which together create a gastronomic experience and strengthen the identity and image of Gresik Regency as a culture and culinary based tourism destination. This study produces a conceptual model of Local Culinary Innovation Based Regional Branding which explains that local culinary innovation acts as a strategic resource in building destination competitiveness and strengthening the regional creative economy. The research findings are expected to serve as a basis for local government and MSME actors in formulating sustainable gastronomic tourism development strategies.